Medusa the rich - Holub, Joan; Williams, Suzanne, 1953- (Holub, Joan. Goddess girls, 2015)
"When Medusa suddenly becomes able to turn objects into gold just by touching them, she is thrilled. Gold, gold, everywhere! But it's not just objects that become golden--it's also food, and, even people! Her new ability turns out to be more dangerous than delightful, but can she do anything to reverse it?" --